The Effectiveness of Implementation of Tax Billing With Forced Letters Based On Law Number 19 Of 2000 on KPP Pratama Makassar Selatan - Septiadica Emisafutry S; Said Sampara; La Ode Husen (Lembaga Sembilan Tiga Community, 2019)
Taxes are a very important source of state revenue. The tax does not only function as a source of state funds but also as a regulator of the smooth running of the country's economy. Tax law is a part of legal science. Tax law in the broad sense is the law relating to tax and in the narrow sense is a set of written legal rules governing the relationship between the tax official and the taxpayer, which contains legal sanctions. Since carrying out tax reforms, state revenue from the tax sector has continued to increase from year to year. Although the awareness of taxpayers is quite good, it has not been satisfactory because the amount of tax revenue generated will be more if the arrears of tax arrears from taxpayers in arrears are settled. The implementation of tax collection by Forced Letter is carried out based on the provisions in Law Number 19 of 1997 concerning Tax Collection by Forced Letter as amended by Law Number 19 of 2000.